Dizziness Handicap and Its Contributing Factors in Patients With Migraine. Issue 5 (28th February 2019) - Lee, Sun Hwa; Kang, Yeonwook; Sohn, Jong‐Hee; Cho, Soo‐Jin
Abstract: Objective: Dizziness is frequently reported in patients with migraine. However, its assessment is often neglected in clinical practice. We investigated the dizziness handicap experienced by patients with migraine and its contributing factors. Methods: A total of 361 migraine outpatients (270 women, 91 men; mean age 39.01 ± 11.2 years) were given the Korean Dizziness Handicap Inventory (KDHI) questionnaire (total score: 100 points; cutoff: 29). The Headache Impact Test, Generalized Anxiety Disorder‐7, Patient Health Questionnaire‐9, and Pittsburgh Sleep Quality Index were also administered. Clinical data such as age, sex, number of headache attacks per month, pain intensity on the visual analog scale, and average sleep hours were collected to find contributing factors. Comparisons were made between chronic and episodic migraine. Results: A total of 153 patients were classified as having dizziness handicap (M+DH) and 208 had migraine without dizziness handicap (M‐DH). Patients with M+DH experienced more headache attacks per month than patients with M‐DH ( P = 0.010). The proportion of patients with chronic migraine was larger in the M+DH group (29.4% vs. 17.3%, P = 0.006). Patients with M+DH showed higher scores than patients with M‐DH in all the KDHI subscales. Multivariable logistic regression showed headache impact, pain intensity, anxiety, and depression to be significantly associated with dizziness handicap. Conclusion: The data suggest that patients with migraine, especially those with chronic‐type migraine, experience physical, emotional, and functional handicaps due to dizziness. Dizziness handicap is related to headache impact, anxiety, and depression. Targeted management of such factors is required to reduce the severity of subjective discomfort.